THE IMPORTANCE OF AWARENESS AND EDUCATION IN MUHAMADIYAH UNIVERSITY OF ENREKANG - Nasrah Nasrah; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
Understanding of education in Indonesia is still very low, especially for people living in remote areas. It's a shame but that's the reality. In the midst of this era of globalization and modernization, technology is increasingly sophisticated and there are still people who do not understand how important education is. Because highly educated people do not have small thoughts about the future, they are future-oriented. Educated people also live by the norms that apply in society. And they know what to do with the future, will not give up or surrender to the circumstances. On the other hand, the community or parents who have a small line of thinking think that education is meaningless, so that it can cause their children who do not have formal education and become a burden to society especially Muhammadiyah University of Enrekang.There are several things that make people tend not to attach importance to education. The first is ignorance of how important education is to survival. Many rural communities think little about formal or non-formal education. Meanwhile, education is very functional to support their lives in the future . The background of parents' awareness of girls' education, namely the low educational background of parents who only graduated from elementary school greatly influences parents' perceptions of the continuation of their children's education which then changes the mindset and decisions they take towards the future of their children, especially to the continuation of children's education. In addition, another factor behind education is socio-cultural, while the background behind the low awareness of the importance of girls' education in particular is the culture of religiosity. There are ways that can be done in overcoming the low awareness of education. That is by holding a socialization about how important formal or non-formal education is for people's lives in this modernization.